Design of A Generator Driven Steam Turbine with A Nominal Power of 10 MW For Industrial Electricity Needs - Frans Denny Manurung (Trigin Publisher, 2020)
Steam turbine is one type of prime mover that is widely used in industry, including: as a prime mover for electric generators, pumps and compressors, as well as process industries. The things that are considered in the use of the steam turbine are the heat source used to evaporate water can be from gas, liquid, and solid fuels, the efficiency of the steam turbine is greater than the gas turbine. The method used in writing this thesis is as follows: (a) ) Field survey, namely in the form of direct observation to the location where the generating unit is located. (b) Literature study, namely in the form of literature study, study of books, and related writings. (c) Discussion, which is in the form of questions and answers with the supervisor, The comparison lecturer who will be appointed by the Department of Cylindrical Mechanical Engineering for small and medium capacity turbines is usually made of gray cast iron JIS G 5501 FC30 with a tensile stress of b 27 kg/mm2 or 2700 kg/cm2 and a safety factor value of k3 (taken) so : b permit 4000/3 1333,33kg/cm2 thus : b permit t , then this construction is safe. From the calculations performed, some conclusions can be drawn in the design of the steam turbine driving the generator: 6.1. Specifications of steam turbine 1. Inlet steam pressure : 42 bar 2. Turbine inlet steam temperature : 480 0 C 3. Turbine outlet steam pressure : 0.1 bar 4. Turbine level : 10 level 5. Extraction amount : 1 level 6. Flow rate steam mass : 12,163 kg/s 7. Turbine power : 12,47 MW 8. Turbine Shaft rotation : 5700 rpm 6.2. Dimensions of the main parts of the turbine: 1.